Foreword - Lida Viganoni (Bollettino della Società Geografica Italiana, 2021)
This special issue of the Bollettino della Società Geografica Italiana completes a research work funded in 2017 for a period of three years by the Ministry of Education, University and Research as part of the 2015 PRIN Program (Research projects of relevant national interest) entitled: Retail, Consumption and Cities: Practices, Planning and Governance for Urban Inclusion, Resilience and Sustainability.